2022
DOI: 10.1155/2022/3647817
|View full text |Cite
|
Sign up to set email alerts
|

The PD-1 with PD-L1 Axis Is Pertinent with the Immune Modulation of Atrial Fibrillation by Regulating T Cell Excitation and Promoting the Secretion of Inflammatory Factors

Abstract: Objective. To analyze the role of PD-1/PD-L1 signaling pathway in regulating T cell activation and secretion of proinflammatory factors in atrial fibrillation. Methods. Forty-five patients with atrial fibrillation admitted to the cardiology department of our hospital from July 2019 to March 2021 were selected to be included in the atrial fibrillation group, and another 45 healthy volunteers were selected as the control group to compare the changes of T cell CD69 and human leukocyte antigen-DR (HLA-DR) expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…51 Many pathogen-induced immunopathological and inflammatory diseases are related to CD 3+ T cell-mediated disorders with an abundance of CD 3+ T cells activating the TLR4 pathway, resulting in the promotion of inflammatory factors like IL-6, IL-17, and TNF-α, which infiltrate the surrounding tissue. 52 Our results showed that acute Vp infection caused increased CD 3+ T cells, overexpression of Tlr2, Tlr4, MyD88, and Nf-κb genes, and increased colonic inflammatory cytokine IL-17 and TNF-α levels. In contrast, FO presupplementation markedly reduced Vp-induced accumulation of CD 3+ T cells in the colonic tissue, alleviated excessive inflammation, and boosted the IFN-γ and IL-4 levels, which are important for the regulation of gut immunological homeostasis.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…51 Many pathogen-induced immunopathological and inflammatory diseases are related to CD 3+ T cell-mediated disorders with an abundance of CD 3+ T cells activating the TLR4 pathway, resulting in the promotion of inflammatory factors like IL-6, IL-17, and TNF-α, which infiltrate the surrounding tissue. 52 Our results showed that acute Vp infection caused increased CD 3+ T cells, overexpression of Tlr2, Tlr4, MyD88, and Nf-κb genes, and increased colonic inflammatory cytokine IL-17 and TNF-α levels. In contrast, FO presupplementation markedly reduced Vp-induced accumulation of CD 3+ T cells in the colonic tissue, alleviated excessive inflammation, and boosted the IFN-γ and IL-4 levels, which are important for the regulation of gut immunological homeostasis.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The homeostasis of intestinal immunity is essential for the integrity of the intestine so that it can recover easily from exposure to gastrointestinal infections. , In this regard, the intestinal epithelial cells, innate immune cells like macrophages, mast cells, and DCs, and in particular adaptive immune cells like T cells (CD 3+ , CD 4+ , and CD 8+ ) play a key role in the recovery from bacterial, fungal, and viral infections . Many pathogen-induced immunopathological and inflammatory diseases are related to CD 3+ T cell-mediated disorders with an abundance of CD 3+ T cells activating the TLR4 pathway, resulting in the promotion of inflammatory factors like IL-6, IL-17, and TNF-α, which infiltrate the surrounding tissue . Our results showed that acute Vp infection caused increased CD 3+ T cells, overexpression of Tlr2 , Tlr4 , MyD88 , and Nf-κb genes, and increased colonic inflammatory cytokine IL-17 and TNF-α levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the programmed cell death 1 (PD-1) and programmed cell death-Ligand 1 (PD-L1) pathways may play immunomodulatory roles in the pathogenesis of AF by regulating T cell excitation and thus promoting cytokine excretion ( 39 ). The above-mentioned findings suggest that the helper T cell population and its cytokines are closely associated with the progression of AF.…”
Section: Discussionmentioning
confidence: 99%